The GBA variant E326K is associated with Parkinson's disease and explains a genome-wide association signal. (29th September 2017) - Berge-Seidl, Victoria; Pihlstrøm, Lasse; Maple-Grødem, Jodi; Forsgren, Lars; Linder, Jan; Larsen, Jan Petter; Tysnes, Ole-Bjørn; Toft, Mathias
Highlights: Two coding variants in the glucocerebrosidase ( GBA ) gene were genotyped in Parkinson's disease (PD) patients and controls. We find an association between the low-frequency GBA variant E326K and PD. Two independent association signals within the chromosome 1 SYT11-GBA locus observed in previous GWAS of PD were genotyped. We find that the GBA variant E326K may fully account for the primary association signal observed at the chromosome 1 SYT11 - GBA locus. Abstract: Objective: Coding variants in the GBA gene have been identified as the numerically most important genetic risk factors for Parkinson's disease (PD). In addition, genome-wide association studies (GWAS) have identified associations with PD in the SYT11-GBA region on chromosome 1q22, but the relationship to GBA coding variants have remained unclear. The aim of this study was to sequence the complete GBA gene in a clinical cohort and to investigate whether coding variants within the GBA gene may be driving reported association signals. Methods: We analyzed high-throughput sequencing data of all coding exons of GBA in 366 patients with PD. The identified low-frequency coding variants were genotyped in three Scandinavian case-controls series (786 patients and 713 controls). Previously reported risk variants from two independent association signals within the SYT11-GBA locus on chromosome 1 were also genotyped in the same samples. We performed association analyses and evaluated linkage disequilibrium (LD) between the variants. Results: We identified six rare mutations (1.6%) and two low-frequency coding variants in GBA . E326K (rs2230288) was significantly more frequent in PD patients compared to controls (OR 1.65, p = 0.03). There was no clear association of T369M (rs75548401) with disease (OR 1.43, p = 0.24). Genotyping the two GWAS hits rs35749011 and rs114138760 in the same sample set, we replicated the association between rs35749011 and disease status (OR 1.67, p = 0.03), while rs114138760 was found to have similar allele frequencies in patients and controls. Analyses revealed that E326K and rs35749011 are in very high LD (r 2 0.95). Conclusions: Our results confirm that the GBA variant E326K is a susceptibility allele for PD. The results suggest that E326K may fully account for the primary association signal observed at chromosome 1q22 in previous GWAS of PD.